THE IMPACT OF SOLAR ENERGY FINANCING ON ELECTRICITY GENERATION IN NIGERIA. AN ARDL APPROACH - Lawal, Ibrahim Ozomata; Bernard, Ojonugwa Anthony; Mustapha, Muktar; Alfa, Yakubu; Oyefabi, Ilemobola (Economics and Statistics Research Journal (ESRJ), 2025)
This study used Auto Regressive Distributed Lag (ARDL) estimation techniques to explore the dynamic relationship between solar energy financing and electricity generation in Nigeria using data from 1985 to 2022. Solar energy financing by the Rural Electrification Agency of Nigeria is the primary independent variable, alongside control variables, such as government expenditure on the electricity sector, renewable energy financing by commercial banks, foreign aid for renewable energy, and labour employed in the electricity sector. The results demonstrate that increases in financing from the Rural Electrification Agency, government spending, commercial bank investments, and foreign aid positively impact electricity generation in both the short and long term. Additionally, labour employed in the sector significantly contributes to the improvement of electricity generation. These findings emphasize the importance of enhancing funding for solar energy projects, diversifying government allocations to the electricity sector, and fostering a supportive environment for foreign aid and investments. Beyond enriching existing literature and theoretical frameworks, this research offers practical insights for policymakers, industry stakeholders, and researchers aiming to promote renewable energy investments for sustainable electricity generation in Nigeria